A New Framework for Joint Trajectory Planning Based on Time-Parameterized B-Splines. (January 2023) - Riboli, Marco; Corradini, Fabio; Silvestri, Marco; Aimi, Alessandra
Abstract: This paper discusses a new, highly effective trajectory planning paradigm for robotics and manufacturing systems. The proposed approach offers a more flexible solution to a problem classically solved in closed-form, defining a generalization of the existing methods by providing a common data structure based on time-parameterized curves to represent exactly or approximately the joint trajectories. In the framework, the most generic approach to constrain or optimize a trajectory is to set up an iterative loop and act on the parameters through computer-aided design concepts, such as shape modeling, symbolic calculation, derivation and integration. The iso-parametric representation allows to define these procedures as macro-instructions to develop scalable and reusable solutions. A benchmark is proposed to confirm the advantages of the new approach over an established solution. Finally, an experimental case study of a single axis motion control is provided to illustrate and clarify the method. Highlights: A new Iso-Parametric Trajectory Planning (IPTP) framework is presented. Time-parameterized univariate B-splines represent trajectories in the joint space. CAD concepts are applied to design and modify the trajectories. IPTP allows both to design mechanical cam profiles and to plan the motion of electric axes. IPTP defines scalable and reusable solutions through macro-instructions definition.